A new generation of smart amine donors for transaminase-mediated biotransformations - Gomm, Andrew; Lewis, William; Green, Anthony P.; O'Reilly, Elaine (Wiley-VCH Verlag, 2016)
The application of ω-transaminase biocatalysts for the synthesis of optically pure chiral amines presents a number of challenges, including difficulties associated with displacing the challenging reaction equilibria. Herein, we report a highly effective approach using low equivalents of the novel diamine donor, cadaverine, which enables high conversions of challenging substrates to the corresponding chiral amines in excellent ee. This approach paves the way for the design of self-sufficient fermentation processes combining transaminase biotransformations with existing strategies for cadaverine production via decarboxylation of endogenous lysine.